KEPUTUSAN KONSUMEN DALAM PEMBELIAN BUAH SEMANGKA DI UD.YASMIN KOTA MATARAM - LUSIANA ANDINI; MADE SUMA WEDASTRA; IDA AYU KETUT MARINI; I DEWA GEDE SUARTHA; BAGUS WIDHI DHARMA S (GANEC SWARA, 2020)
This research is a descriptive study which aims to determine consumer decisions in purchasing watermelons at UD Yasmin Mataram City. This study used a sample of 50 people who were determined by incidental sampling. Data collection techniques are carried out by: observation and interview based on a list of questions that have been prepared in advance and documentation. The collected data were analyzed using descriptive analysisThe results showed that: the decisions that influence consumers to purchase watermelons at UD Yasmin Mataram City are: 50% of respondents strongly agree and 42% agree to product variables; 40% of respondents agreed and 44% strongly agreed because of the price variable; 52% of respondents agreed and 30% stated that they strongly agreed because of the variable of place and 44% of respondents agreed and 36% strongly agreed to buy watermelons at UD Yasmin because of the promotional variables. It is recommended that UD Yasmin keep product continuity and maintain product quality and maintain price stability